2006
DOI: 10.1128/mcb.00326-06
|View full text |Cite
|
Sign up to set email alerts
|

TReP-132 Is a Novel Progesterone Receptor Coactivator Required for the Inhibition of Breast Cancer Cell Growth and Enhancement of Differentiation by Progesterone

Abstract: The sex steroid progesterone is essential for the proliferation and differentiation of the mammary gland epithelium during pregnancy. In relation to this, in vitro studies using breast carcinoma T47D cells have demonstrated a biphasic progesterone response, consisting of an initial proliferative burst followed by a sustained growth arrest. However, the transcriptional factors acting with the progesterone receptor (PR) to mediate the progesterone effects on mammary cell growth and differentiation remain to be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…In the case of p21 CIP1 , progestins modulate its expression via PR tethering to the TF SP1 at the third and fourth SP1 binding sites in the p21 CIP1 promoter [86 -88] . Similar interaction between PR and SP1 at the p27 KIP1 promoter has also been found [87] . The coactivators CBP/p300 and TReP-132 are corecruited along with SP-1 and PR to p21 CIP1 and p27 KIP1 promoters [87] .…”
Section: Non-classical Pr Tethering Transcriptional Mechanismssupporting
confidence: 67%
See 1 more Smart Citation
“…In the case of p21 CIP1 , progestins modulate its expression via PR tethering to the TF SP1 at the third and fourth SP1 binding sites in the p21 CIP1 promoter [86 -88] . Similar interaction between PR and SP1 at the p27 KIP1 promoter has also been found [87] . The coactivators CBP/p300 and TReP-132 are corecruited along with SP-1 and PR to p21 CIP1 and p27 KIP1 promoters [87] .…”
Section: Non-classical Pr Tethering Transcriptional Mechanismssupporting
confidence: 67%
“…Similar interaction between PR and SP1 at the p27 KIP1 promoter has also been found [87] . The coactivators CBP/p300 and TReP-132 are corecruited along with SP-1 and PR to p21 CIP1 and p27 KIP1 promoters [87] . This tethering mechanism raises an exciting question: does PR rapid stimulation of signaling pathways induce the phosphorylation of TFs that in turn participate in non-classical PR transcriptional tethering mechanisms ?…”
Section: Non-classical Pr Tethering Transcriptional Mechanismssupporting
confidence: 67%
“…We observed that the anti-inflammatory actions of PR are mediated by ligand-dependent and -independent mechanisms, resulting in an inhibition of NF-B activation with consequent down-regulation of hCOX-2, aromatase/hCYP19, and HER-2/neu expression (44). Notably, MKP-1 mRNA expression was observed to be induced by P 4 /PR in human breast cancer cells (22).…”
mentioning
confidence: 87%
“…Within the nuclear compartment, NCOR2 participates in a co-repressor complex resulting in chromatin condensation and may also modulate ligand dependency of hormone receptors and contribute to estrogen independency [34][35][36]. TRERF1 was reported to negatively modulate breast cancer cell proliferation by upregulation of G1 cyclin-dependent kinase inhibitors and through co-activation of the progesterone receptor [23,37]. Whether the transcription regulators CITED2 and TLE3 fit into the same pathways as the cytoplasmic targets or represent alternative signaling routes, remains an intriguing question.…”
Section: Mechanisms Of Estrogen Independence Of Breast Cancer Cellsmentioning
confidence: 99%